The Biodiversity of Retreating Glaciers Leaves an Ecological Legacy in Emerging Soil Communities - Isabel Cantera; Silvio Marta; Alexis Carteron; Alessia Guerrieri; Simone Giachello; Aurélie Bonin; Roberto Ambrosini; Roberto Sergio Azzoni; Marco Caccianiga; Francesca Pittino; Andrea Simonicini; Barbara Valle; et al. (Global Change Biology, 2026)
Glacier retreat is transforming high‐mountain and polar landscapes, replacing ice with vast, newly exposed terrains where soil development and ecological succession start. Although ecosystems developing in deglaciated terrains are often viewed as starting from scratch, glaciers host diverse communities whose links with emerging soils remain unquantified. Using environmental DNA metabarcoding, we provide the first multi‐taxa assessment of biodiversity transitions across the supraglacial–proglacial interface across five glacier systems in Svalbard, the Alps and Patagonia. We analysed 212 samples from the surfaces of retreating glaciers and their forelands, spanning a chronosequence from 1 to 483 years since deglaciation. Recently deglaciated soils (≤ 10 years since glacier retreat) showed taxonomic and functional similarity to supraglacial communities. This ecological continuity was highly taxon‐specific, being pronounced for communities of microorganisms (Bacteria, Fungi, Protista) but weak for animals (e.g., Collembola, Insecta). For microbes, similarity diminished rapidly over succession as community turnover increased, and functional composition shifted from phototrophic and saprotrophic dominance toward heterotrophic and symbiotic assemblages. Shared microbial taxa and functions indicate a transient glacial influence during early soil succession. Our results suggest that early soil communities are not assembled independently of glacier ecosystems, but are initially linked to them through diverse ecological pathways that diminish over time. The observed glacier–proglacial connectivity challenges the view of succession on deglaciated terrains as beginning on lifeless substrates and instead points to a glacial legacy in emerging soils. As glaciers rapidly disappear under climate change, the unique biodiversity they host is also being lost, underscoring the urgent need to study supraglacial and proglacial systems together. Such integration is essential to understand ecological succession in proglacial ecosystems, which are expected to play an increasingly important role in this century.

Effects of local management and landscape factors on taxonomic and functional diversity of multiple taxa in managed grasslands - Matteo Conti; Andrea Dalpasso; Alberto Mattia Nodari; Isabel Cantera; Benedetta Barzaghi; Mattia Brambilla; Andrea Ferrari; Gentile Francesco Ficetola; Simone Giachello; Elia Lo Parrino; Valeria Messina; Carlo Polidori; et al. (Agriculture, Ecosystems & Environment, 2026)

Species distribution models for the conservation of a micro-endemic animal: the contribution of regional land cover - Simone Giachello; Sara Lefosse; Andrea Simoncini; Lucio Bonato (Biodiversity and Conservation, 2025)
Micro-endemic animals face high extinction risks. Species distribution models offer powerful tools for effective conservation strategies, but their implementation is hindered by the resolution of environmental data such as land cover. Here, we assessed the efficacy of one regional versus two continental land cover datasets in predicting habitat suitability for Salamandra atra aurorae , a fully terrestrial amphibian endemic to a ca. 30 km 2 area in Northern Italy. We built three species distribution models with the same spatial resolution of 100 × 100 m using the same topographic and climatic predictors but varying the land cover dataset describing forest classes. We used a composite regional dataset assembled from local sources, the Corine Land Cover and the Sentinel-2 Global Land Cover, and compared their capacity to identify the ecological requirements of the species. The models performed comparably, identifying elevation, temperature, and tree composition as primary drivers of habitat suitability and predicting similar suitable areas. However, while all models recognized coniferous forests as more suitable than broadleaf forests, only the land cover classification of the regional dataset allowed to identify different suitability among coniferous forests. Notably, the model using the regional dataset identified old-growth stands with Abies alba as the most suitable, aligning with previous ecological studies. Our case study highlights the limitations of widely used continental land cover datasets in recognising key environmental features influencing habitat suitability for a micro-endemic animal. We showed that incorporating regional land cover data can enhance the accuracy of species distribution models providing more detailed ecological information to guide conservation efforts.

Describing functional diversity of communities from environmental DNA - Isabel Cantera; Simone Giachello; Tamara Münkemüller; Marco Caccianiga; Mauro Gobbi; Gianalberto Losapio; Silvio Marta; Barbara Valle; Krzysztof Zawierucha; Wilfried Thuiller; Gentile Francesco Ficetola (Trends in Ecology & Evolution, 2025)

Functional changes of protist communities in soil after glacier retreat - Simone Giachello; Isabel Cantera; Alexis Carteron; Aurelie Bonin; Alessia Guerrieri; Roberto Ambrosini; Marco Caccianiga; Mauro Gobbi; Silvio Marta; Gentile Francesco Ficetola (Science of The Total Environment, 2024)

Integrating historical and recent data to measure long-term trends of endangered subterranean species - Gentile Francesco Ficetola; Raoul Manenti; Benedetta Barzaghi; Samuele Romagnoli; Elia Lo Parrino; Andrea Melotto; Silvio Marta; Simone Giachello; Valentina Balestra; Enrico Lana; Luigi Maiorano; Roberta Pennati; et al. (Biological Conservation, 2024)

Toward a common set of functional traits for soil protists - Simone Giachello; Isabel Cantera; Alexis Carteron; Silvio Marta; Cristina Cipriano; Alessia Guerrieri; Aurélie Bonin; Wilfried Thuiller; Gentile Francesco Ficetola (Soil Biology and Biochemistry, 2023)

Long‐term drivers of persistence and colonization dynamics in spatially structured amphibian populations - Mattia Falaschi; Simone Giachello; Elia Lo Parrino; Martina Muraro; Raoul Manenti; Gentile Francesco Ficetola (Conservation Biology, 2021)
Many organisms live in networks of local populations connected by dispersing individuals, called spatially structured populations (SSPs), where the long‐term persistence of the entire network is determined by the balance between 2 processes acting at the scale of local populations: extinction and colonization. When multiple threats act on an SSP, a comparison of the different factors determining local extinctions and colonizations is essential to plan sound conservation actions. We assessed the drivers of long‐term population dynamics of multiple amphibian species at the regional scale. We used dynamic occupancy models within a Bayesian framework to identify the factors determining persistence and colonization of local populations. Because connectivity among patches is fundamental to SSPs dynamics, we considered 2 measures of connectivity acting on each focal patch: incidence of the focal species and incidence of invasive crayfish. We used meta‐analysis to summarize the effect of different drivers at the community level. Persistence and colonization of local populations were jointly determined by factors acting at different scales. Persistence probability was positively related to the area and the permanence of wetlands, whereas it was negatively related to occurrence of fish. Colonization probability was highest in semipermanent wetlands and in sites with a high incidence of the focal species in nearby sites, whereas it showed a negative relationship with the incidence of invasive crayfish in the landscape. By analyzing long‐term data on amphibian population dynamics, we found a strong effect of some classic features commonly used in SSP studies, such as patch area and focal species incidence. The presence of an invasive non‐native species at the landscape scale emerged as one of the strongest drivers of colonization dynamics, suggesting that studies on SSPs should consider different connectivity measures more frequently, such as the incidence of predators, especially when dealing with biological invasions.